Clinical practice guidelines in the diagnosis and management of acute pancreatitis - Kinoshita, Hiroyuki; Zhang, Jianhua; Ponthisarn, Aroon; Sharma, Manoj; Binh, Nguyen; Siam, Alex; Samaranayake, Chandika; Darnindro, Arnold; Barnes, Michael (Medical Studies/Studia Medyczne, 2019)
Acute pancreatitis (AP) continues to be a cause of significant morbidity and mortality and requires more research to identify the best clinical management practices. Many guidelines have been proposed for the initial management of AP. Although these guidelines have a significant overlap in the recommendations provided for diagnosing and managing AP, there is still some disagreement in aspects of the types and timing of interventions that should be used for the diagnosis and management of both mild and severe AP. A working group consisting of physicians, especially gastroenterologists from various hospitals and universities from the Asia-Pacific region, has led to the development of these evidence-based guidelines and recommendations. Early enteral feedings, performing a cholecystectomy in the case of gallstones if indicated during the initial hospitalisation, treatment of hypertriglyceridaemia-induced acute pancreatitis using intravenous regular insulin or plasmapheresis if severe, and providing counselling for alcohol avoidance are recommended.